1980
DOI: 10.1136/bjsm.14.4.199
|View full text |Cite
|
Sign up to set email alerts
|

Age of menarche in various categories of Indian sportswomen.

Abstract: Data on the age of menarche has been collected on 264 Indian sportswomen, and 108 girls forming the control group, all hailing from the Punjab, Haryana, chandigarh and Delhi. Outstanding athletes and players of hockey, basketball and volleyball were included. The combined mean age at menarche for sportswomen is 15.21 years and for the control sample is 14.05 years. The differences in the two series are statistically significant. The mean age at menarche in hockey, basketball, volleyball and athletes is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The age at menarche is widely considered as an important landmark in sexual maturity (Sidhu and Grewal, 1980). However, it varies widely, even within the same population and is influenced by many factors like climate, geographical, socioeconomic conditions and many other factors of genetic and non-genetic nature (Mehta et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The age at menarche is widely considered as an important landmark in sexual maturity (Sidhu and Grewal, 1980). However, it varies widely, even within the same population and is influenced by many factors like climate, geographical, socioeconomic conditions and many other factors of genetic and non-genetic nature (Mehta et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of the study and analysis of data the following four groups were constituted: Group A: Control subjects (non-athletes) Group B: Combined samples of athletes Group C: Athletes with regular sports starting before menarche Group D: Athletes with regular sports only after menarche participation participation The test for significance in the difference between the means of various groups was calculated by using a 't' test. (1973) and Sidhu and Grewal (1980). It is obvious from Table II that with the exception of jumpers, athletes of different activity groups in Group C had significantly delayed onset of menstruation, expecially ball game players and throwers.…”
Section: Introductionmentioning
confidence: 93%
“…Further, Malina et al (1978) noted that college athletes attained menarche significantly later than non-athletes and various groups of national and Olympic athletes attained menarche significantly later than high school and college athletes. Sidhu and Grewal (1980) In this study, an attempt has been made to determine whether menarcheal age of Nigerian women athletes differs from that of non-athletes. This would afford an understanding of the probable influence of physical exercise on the menarcheal age.…”
Section: Introductionmentioning
confidence: 99%
“…For example, data from a review (Malina, 1985) of seventeen studies found that menarche occured later in athletes compared to the general population, suggesting that training delays menarche. In addition, studies by Frisch, et al (1981) and Sidhu and Grewal (1980) found menarchal age occurred later among athletes who began training before menarche as compared to athletes who began training after menarche.…”
Section: Performance and Training Volumementioning
confidence: 99%
“…To further this point, studies (Frisch, et al, 1981;Sidhu and Grewal, 1980) indicate later mean menarchal ages among athletes who began training before menarche as compared to athletes who began training after menarche. It is not surprising that menarche is also significantly related to skeletal maturity (Tanner, 1962;Malina, 1978), but the results of these studies and the other studies noted illustrate how highly complex the association between menarche and amenorrhea can be.…”
Section: Amenorrheamentioning
confidence: 99%